Detecção de ruídos em repositórios de máquina de busca - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
Search engines are among the most used tools to find information on the Web. Recent studies show that the user s confidence on these systems is high. However, the database of search engines usually contains noisy information that may decrease the search results quality and thus negatively affect the confidence of users in these systems. Such type of information is called noise and it can be intentional or not. The main goals of this thesis are to develop and enhance techniques to detect noise in databases of search engines. We evaluated noisy sources of information that may be present either in the anchor text and/or links structures of search engine indexes. As a result, we present methods to turn search engines less susceptible of negative impact caused by the presence of noisy.
Keywords: Máquina de Busca; Search engine; Repositórios de máquinas de busca; CIÊNCIAS EXATAS E DA TERRA: CIÊNCIA DA COMPUTAÇÃO